Impact and collaboration in environmental research: moving universities from evidence producers to co-producers - Troiano, M; Sidwell, N; Boyle, J; James, M; Wright, G; Barbrook-Johnson, P; Hirons, M (Agile Initiative, Oxford Martin School, 2024)
This discussion paper explores the relationship between environmental research and its use in environmental policy. While there is a common perception of a gap between research and policy, efforts to bridge it often fall short of integrating knowledge effectively with environmental action. Common fixes, like improving dissemination and scientific literacy within government, overlook the politics and complexities of knowledge production and usage. We explore universities’ pivotal position in the science-policy ecosystem, particularly given their role in knowledge brokerage practices and the influence of ‘impact’ as a governance tool. Participatory approaches, such as co-production, offer promise for closing the ‘usability gap’ for research by facilitating collaborative generation of actionable knowledge. Co-production features high user participation, contributing to higher-quality research, fostering trust, and giving voice to knowledge users and interested parties. Understood and deployed in various ways, co-production also faces challenges such as the high potential costs or replication of wider knowledge production risks. A reflective approach to co-production, considering positionality and recognising political influences, can mitigate these risks and optimise its benefits. We highlight the potential of co-production in environmental research and policy and offers valuable insights and recommendations for its effective implementation. We hope that the material in this discussion paper provides a constructive basis for precipitating reflections and discussions amongst researchers and other people involved in the production and use of environmental research about their role in engaging with policy.